Examining the Spatial Distribution of IPARD II Supports for Agriculture and Rural Development in Türkiye - Pelin Albayrak Fakıoğlu; Ebru Seçkin (Coğrafya Dergisi)
The European Union’s (EU) Instrument for Pre-Accession Assistance on Rural Development (IPARD) program that came into effect in 2007 has been applied in Türkiye since 2011. The aim of IPARD is to increase the amount of regionally suitable investments through local initiatives. In this respect, IPARD has great potential to act as leverage in agriculture and rural development. However, this evaluation must figure out how these grants are utilized. This study seeks to answer whether EU funds have a leveraging effect on rural development. Accordingly, the paper aims to analyze the distribution patterns of IPARD grants in Türkiye and to investigate whether or not regional discrepancies exist among the types of grants. This paper covers the period of IPARD II from 2016-2020 in detail due to detailed information (i.e., city, grant type) only being able to be found regarding IPARD II. Correspondingly, the article descriptively analyzes the total of 4,028 projects that were supported between 2016-2020. In conclusion, some cities (i.e., Konya, Samsun, Afyonkarahisar) are seen to have outshined others, with less-developed cities in Eastern Türkiye in particular having received fewer grants than others. Another important conclusion of this study is that the amount of grants under the heading of Measures for Farm Diversification and Business Development was greater than for other headings. This indicates that a new path should be created for Türkiye’s rural development, one that is based not solely on agriculture but also on agriculture-related sectors.